Positive electrode for alkaline secondary battery and alkaline secondary battery having the positive electrode
By using specific anatase-type titanium oxide particles as additives in the positive electrode of an alkali secondary battery, the problem of decreasing capacity recovery rate caused by overdischarge in high temperature environments is solved, and the durability of the battery is improved.
Patent Information
- Application Number
- CN201980061562.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-21
- Filing Date
- 2019-08-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2039-08-15
AI Technical Summary
In high temperature environments, the alkaline secondary battery is reduced by overdischarge, the conductive network is destroyed, the utilization rate of the positive electrode active substance is reduced, resulting in a decrease in capacity recovery rate.
A positive electrode additive containing anatase-type titanium oxide particles is used, the average particle size of the titanium oxide particles is between 5 nm and 10 nm, the BET specific surface area is between 230 m2/g and 360 m2/g, and it contains more than 0.1% of niobium, and the addition rate relative to nickel hydroxide is between 0.1% and 1.0%.
Even if it is repeatedly placed in a high temperature environment, the decline in capacity recovery rate can be suppressed and the durability of the battery is improved.
Smart Images

Figure CN112740441B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode for an alkaline secondary battery and an alkaline secondary battery including the positive electrode. Background Art
[0002] In the positive electrode for alkaline secondary batteries, nickel hydroxide is used as the positive electrode active material. Since the conductivity of the nickel hydroxide is low, it is difficult to improve the utilization rate of the positive electrode active material when only nickel hydroxide is used. Therefore, in order to impart conductivity, the cobalt compound is generally precipitated on the surface of the nickel hydroxide particles and then oxidized to form a conductive layer. The conductive layers on the surfaces of the nickel hydroxide particles form a conductive network by contacting each other. Thereby, the conductivity of the positive electrode is improved, and the utilization rate of the positive electrode active material is improved.
[0003] However, the use of alkaline secondary batteries as battery packs composed of multiple alkaline secondary batteries is increasing. For example, there are power sources for driving electric vehicles, power storage systems for renewable energy, backup power sources for power outages, etc. For such battery packs, the reaction heat and Joule heat caused by the battery reaction are generated along with charging and discharging, the temperature tends to rise, and they are often exposed to high temperatures. In addition, in recent years, with the further expansion of uses, alkaline secondary batteries are increasingly used in more severe environments, such as high temperature environments. In particular, there is a situation where they are over-discharged when placed in a high temperature environment with a load connected.
[0004] If the alkaline secondary battery is over-discharged like this, the above-mentioned cobalt compound will be reduced, the conductive network will be destroyed, and the utilization rate of the positive electrode active material will be reduced. Especially in a high temperature environment, the destruction of the conductive network is easier to carry out. If the utilization rate of the positive electrode active material is reduced, the charge acceptance will be reduced, and the capacity of the alkaline secondary battery will be reduced. In this case, even if it is charged again, the initial capacity cannot be ensured. That is, the capacity recovery rate decreases.
[0005] In order to avoid such problems, it is considered effective to inhibit the reduction of cobalt compounds. Therefore, various studies have been conducted on methods for inhibiting the reduction of cobalt compounds. As an example of such a method for inhibiting the reduction of cobalt compounds, it is known to add compounds such as Ti, Nb, W, Y, and Yb to the positive electrode mixture (for example, refer to Patent Document 1). That is, by adding compounds such as Ti, Nb, W, Y, and Yb as additives to the positive electrode mixture, it is expected to suppress the reduction of the capacity of the alkaline secondary battery.
[0006] When the additive is used, the destruction of the conductive network can be suppressed to a small extent, so that even if the battery is charged again, a capacity close to the initial capacity can be ensured, and a decrease in the capacity recovery rate can be suppressed.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2004-031292 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] However, some devices equipped with the battery pack may be used in more severe ways, such as leaving the alkaline secondary battery connected to a load in a high temperature environment for a long time, and such long-term leaving may be repeated many times.
[0012] When the additives described above are used, the decrease in capacity recovery rate can be suppressed if the frequency of long-term placement of the alkaline secondary battery in a high temperature environment with a load connected is as low as about once. However, the current situation is that the decrease in capacity recovery rate cannot be suppressed if the long-term placement described above is repeated many times.
[0013] Therefore, it is desired to develop an alkaline secondary battery that can suppress a decrease in capacity recovery rate even under such severe usage patterns as described above.
[0014] The present invention has been made based on the above circumstances, and an object of the present invention is to provide a positive electrode for an alkaline secondary battery and an alkaline secondary battery having the positive electrode, which can suppress a decrease in capacity recovery rate even when repeatedly left for a long period of time in a high temperature environment with a load connected.
[0015] Technical solutions adopted to solve technical problems
[0016] According to the present invention, a positive electrode for an alkaline secondary battery is provided, which comprises a positive electrode substrate and a positive electrode mixture supported on the positive electrode substrate, wherein the positive electrode mixture comprises a positive electrode active material, nickel hydroxide, and a positive electrode additive, wherein the positive electrode additive comprises titanium oxide particles having an anatase crystal structure, wherein the primary particles of the titanium oxide particles have an average particle size of 5 nm or more and 10 nm or less, and a BET specific surface area of 230 m 2 / g above 360m 2 / g or less, the titanium oxide particles contain 0.1 mass % or more of niobium, and the addition rate of the titanium oxide to the nickel hydroxide is 0.1 mass % or more and 1.0 mass % or less.
[0017] It is also preferred that the purity of the titanium oxide is 90 mass % or more and 95 mass % or less.
[0018] According to the present invention, there is also provided an alkaline secondary battery comprising an outer can and an electrode group accommodated in the outer can together with an alkaline electrolyte, the electrode group including a positive electrode and a negative electrode stacked with a separator, the positive electrode being any one of the positive electrodes for alkaline secondary batteries described above.
[0019] Effects of the Invention
[0020] The positive electrode for alkaline secondary battery of the present invention comprises a positive electrode substrate and a positive electrode mixture supported on the positive electrode substrate, wherein the positive electrode mixture comprises a positive electrode active material nickel hydroxide and a positive electrode additive, wherein the positive electrode additive comprises titanium oxide particles having an anatase crystal structure, wherein the average particle size of the primary particles of the titanium oxide particles is not less than 5 nm and not more than 10 nm, and the BET specific surface area is not less than 230 m 2 / g above 360m 2 / g or less, and the titanium oxide particles contain 0.1 mass % or more of niobium, and the addition rate of the titanium oxide relative to the nickel hydroxide is 0.1 mass % or more and 1.0 mass % or less. Even if the alkaline secondary battery including the positive electrode using the positive electrode additive that satisfies the above conditions is repeatedly placed for a long time in a high temperature environment in a state connected to a load, the decrease in capacity recovery rate can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 FIG. 1 is a partially cutaway perspective view of a nickel-hydrogen secondary battery according to an embodiment of the present invention. DETAILED DESCRIPTION
[0022] Hereinafter, an alkaline secondary battery to which the present invention is applicable will be described with reference to the accompanying drawings. The alkaline secondary battery to which the present invention is applicable is not particularly limited. Figure 1 The case of a cylindrical nickel-hydrogen secondary battery (hereinafter referred to as a battery) 2 of the AA size shown will be described as an example.
[0023] like Figure 1 As shown, the battery 2 has an outer can 10, which is in the shape of a bottomed cylindrical body with an opening at the top. The outer can 10 is conductive, and its bottom wall 35 serves as a negative terminal. A sealing body 11 is fixed at the opening of the outer can 10. The sealing body 11 includes a cover plate 14 and a positive terminal 20, which provides the positive terminal 20 while sealing the outer can 10. The cover plate 14 is a conductive circular plate-shaped member. The opening of the outer can 10 is provided with a cover plate 14 and an annular insulating gasket 12 surrounding the cover plate 14, and the insulating gasket 12 is fixed to the opening edge 37 of the outer can 10 by performing a caulking process (Japanese: かしめ processing) on the opening edge 37 of the outer can 10. That is, the cover plate 14 and the insulating gasket 12 cooperate with each other to seal the opening of the outer can 10 airtightly.
[0024] Here, the cover plate 14 has a central through hole 16 at its center. A rubber valve body 18 is disposed on the outer surface of the cover plate 14 to block the central through hole 16. A metal positive electrode terminal 20 in a cylindrical shape with a flange is also provided on the outer surface of the cover plate 14 and is electrically connected to the valve body 18 in a manner covering the valve body 18. The positive electrode terminal 20 presses the valve body 18 toward the cover plate 14. In addition, a vent hole opening (not shown) is also provided on the positive electrode terminal 20.
[0025] Normally, the central through hole 16 is hermetically sealed by the valve body 18. When gas is generated in the outer can 10 and the internal pressure thereof increases, the valve body 18 is compressed by the internal pressure, causing the central through hole 16 to open, resulting in the gas being discharged from the outer can 10 to the outside through the central through hole 16 and the exhaust hole (not shown) of the positive terminal 20. That is, the central through hole 16, the valve body 18 and the positive terminal 20 form a safety valve for the battery.
[0026] The outer can 10 contains an electrode group 22. The electrode group 22 includes a strip-shaped positive electrode 24, a negative electrode 26, and a separator 28, and is wound in a spiral shape with the separator 28 sandwiched between the positive electrode 24 and the negative electrode 26. That is, the positive electrode 24 and the negative electrode 26 overlap each other with the separator 28 interposed therebetween. The outermost periphery of the electrode group 22 is formed by a portion (outermost periphery) of the negative electrode 26, which contacts the inner peripheral wall surface of the outer can 10. That is, the negative electrode 26 and the outer can 10 are electrically connected to each other.
[0027] In the outer can 10, a positive electrode lead 30 is arranged between one end of the electrode group 22 and the cover plate 14. Specifically, one end of the positive electrode lead 30 is connected to the positive electrode 24, and the other end is connected to the cover plate 14. Therefore, the positive electrode terminal 20 and the positive electrode 24 are electrically connected to each other through the positive electrode lead 30 and the cover plate 14. In addition, a circular upper insulating member 32 is arranged between the cover plate 14 and the electrode group 22, and the positive electrode lead 30 extends through a slit 39 provided on the upper insulating member 32. In addition, a circular lower insulating member 34 is also arranged between the electrode group 22 and the bottom of the outer can 10.
[0028] Furthermore, a predetermined amount of alkaline electrolyte (not shown) is injected into the outer can 10. The alkaline electrolyte impregnates the electrode group 22 to allow the charge and discharge reaction between the positive electrode 24 and the negative electrode 26 to proceed. As the alkaline electrolyte, an alkaline electrolyte containing KOH, NaOH, LiOH, etc. as a solute is preferably used.
[0029] As the material of the spacer 28, for example, a material obtained by imparting a hydrophilic functional group to a polyamide fiber nonwoven fabric, a material obtained by imparting a hydrophilic functional group to a polyolefin fiber nonwoven fabric such as polyethylene or polypropylene, or the like can be used.
[0030] The positive electrode 24 includes a positive electrode substrate and a positive electrode mixture supported on the positive electrode substrate.
[0031] The positive electrode substrate is formed of a conductive material having a three-dimensional mesh structure. Specifically, a nickel-plated mesh, sponge, or fiber-shaped metal body or foamed nickel can be used as the positive electrode substrate.
[0032] The positive electrode mixture includes positive electrode active material particles, positive electrode additives and a binder. The binder serves to bond the positive electrode active material particles and the positive electrode additive to the positive electrode substrate. Here, as a binder, for example, carboxymethyl cellulose, methyl cellulose, PTFE (polytetrafluoroethylene) dispersion, HPC (hydroxypropyl cellulose) dispersion, etc. can be used.
[0033] Nickel hydroxide particles or high-order nickel hydroxide particles are used as the positive electrode active material particles. Zinc or cobalt is preferably dissolved in these nickel hydroxide particles as required.
[0034] In one embodiment, a conductive layer containing a cobalt compound is formed on the surface of the nickel hydroxide particles. As the cobalt compound, cobalt hydroxide (Co(OH) 2 ) and cobalt oxide (CoO), etc. In order to make the cobalt compound of the conductive layer less easily reduced, it is preferably made high-order in advance.
[0035] The positive electrode additive plays a role in suppressing the reduction of the cobalt compound in the conductive layer and suppressing the destruction of the conductive network. The positive electrode additive of the present invention includes titanium oxide.
[0036] The crystal structures of titanium oxide include rutile, anatase and brookite. Among them, rutile and anatase titanium oxides are more common. Of these two crystal structures, the present invention uses anatase titanium oxide. Batteries added with rutile titanium oxide and batteries added with anatase titanium oxide show basically similar characteristics. From the capacity recovery rate when the battery is placed in a state connected to a load, rutile titanium oxide and anatase titanium oxide also show the same capacity recovery rate when placed for the first time.
[0037] However, in the case of repeatedly placing the battery in a state connected to a load or reverse charging such as a use form in which the reduction of the cobalt compound cannot be avoided, the capacity recovery rate is improved when using anatase titanium oxide compared to the case of using rutile titanium oxide. It is believed that this is because anatase titanium oxide plays a role in suppressing the reduction of the cobalt compound layer on the surface of the positive electrode active material particles and making the reduced cobalt compound easy to return to the oxidized state, that is, improving the reversibility. In addition, compared with rutile titanium oxide, the specific surface area of anatase titanium oxide is easy to increase, which is beneficial to improving the characteristics in the battery. In this way, when using anatase titanium oxide, even if the battery is repeatedly placed in a high temperature environment in a state connected to a load, the capacity recovery rate decreases less, and the effect of improving battery durability can be obtained.
[0038] If the anatase titanium oxide has an average primary particle size of 5 nm or more and 10 nm or less and a BET specific surface area of 230 m 2 / g or more, the above effect will be more significant. In addition, the upper limit of the BET specific surface area of anatase titanium oxide is 360m 2 This is because the current industrial manufacturing method is difficult to prepare BET specific surface area greater than 360m 2 / g of anatase titanium oxide.
[0039] Here, the average particle size in the present invention refers to the volume average particle size obtained by measuring the particle size distribution of the aggregate of the object particles, i.e. the powder, with a laser diffraction and scattering particle size distribution measuring device on a volume basis. In addition, the BET specific surface area refers to the specific surface area measured by the nitrogen adsorption BET method using a specific surface area measuring device.
[0040] In addition, it is preferred to use titanium oxide having a purity of 90% by mass or more and 95% by mass or less. If the purity of titanium oxide is 90% by mass or more, the capacity recovery rate when repeatedly placed as described above will not decrease significantly, and it can be fully used. On the other hand, when the purity is too high, the inhibitory effect of the decrease in the capacity recovery rate when repeatedly placed as described above is reduced. Therefore, the purity of titanium oxide is preferably 95% by mass or less.
[0041] Here, the purity of titanium oxide is expressed as the content of titanium oxide after dehydration and drying. In the present invention, the content of titanium oxide after dehydration and drying refers to the content obtained by heating the titanium oxide sample used to 105°C, keeping it for 24 hours to dry it, and then measuring it in accordance with 7.2 of Japanese Industrial Standard (JIS) K5116. Specifically, the titanium oxide material commonly circulated mainly includes titanium oxide, and also includes titanium oxide hydrate or titanium hydroxide. The amount of titanium oxide contained in the titanium oxide material is the amount expressed in mass fraction calculated from the titanium oxide equivalent, which is used as the titanium oxide content, that is, the purity.
[0042] In addition, the size of secondary particles of titanium oxide is usually 3.0 μm or less, regardless of the size of primary particles.
[0043] Furthermore, the titanium oxide of the present invention contains 0.1 mass % or more of niobium, and the niobium is dissolved in the titanium oxide in the form of niobium oxide.
[0044] The content of niobium dissolved in titanium oxide is preferably 0.1 mass % or more and 1.0 mass % or less. This is because when the niobium content is less than 0.1 mass %, the effect of suppressing the decrease in capacity recovery rate is small, while when the niobium content is more than 1.0 mass %, the effect of suppressing the decrease in capacity recovery rate is saturated.
[0045] In addition, if titanium oxide as the above-mentioned positive electrode additive is added in an amount of 0.1 mass % to 1.0 mass % relative to the positive electrode active material nickel hydroxide, even if the battery is repeatedly placed in a high temperature environment with a load connected, the capacity recovery rate will decrease less, which can further improve the effect of improving the battery durability.
[0046] It is preferable to add rare earth substances such as yttrium oxide as other components to the positive electrode additives because, for example, yttrium oxide can make the effect of the above-mentioned titanium oxide more stable.
[0047] The yttrium oxide is particles having an average particle size of 1 μm to 5 μm. Yttrium oxide powder having a particle size of 90% of the particles being 20 μm or less is prepared. The yttrium oxide powder is mixed with the titanium oxide powder to obtain a positive electrode additive.
[0048] Here, if yttrium oxide is added in an amount of 0.1 mass % to 1.0 mass % with respect to nickel hydroxide, which is the positive electrode active material, the effect of the titanium oxide can be further stabilized.
[0049] The positive electrode 24 can be produced, for example, as follows.
[0050] First, a positive electrode additive, water and a binder are added to a positive electrode active material particle assembly, i.e., a positive electrode active material powder, and kneaded to form a positive electrode mixture slurry. The obtained positive electrode mixture is filled into, for example, foamed nickel and dried. After drying, the foamed nickel filled with nickel hydroxide particles is rolled and then cut. Thus, a positive electrode 24 carrying the positive electrode mixture is obtained.
[0051] Next, the negative electrode 26 will be described.
[0052] The negative electrode 26 has a strip-shaped conductive negative electrode core material, and the negative electrode core material holds a negative electrode mixture.
[0053] The negative electrode core material is a sheet-like metal material with distributed through holes, such as a perforated metal sheet. The negative electrode mixture is not only filled in the through holes of the negative electrode core material, but also maintained in a layered form on both surfaces of the negative electrode core material.
[0054] The negative electrode mixture includes hydrogen storage alloy particles, a conductive material and a binder. The hydrogen storage alloy particles can store and release hydrogen as a negative electrode active material. The binder not only bonds the hydrogen storage alloy particles, the negative electrode additive and the conductive material to each other, but also plays a role in bonding the negative electrode mixture to the negative electrode core material. Here, a hydrophilic or hydrophobic polymer can be used as a binder, and carbon black or graphite can be used as a conductive material. In addition, a negative electrode additive can be added as needed.
[0055] As the hydrogen storage alloy in the hydrogen storage alloy powder, those used in conventional nickel-hydrogen secondary batteries are suitably used.
[0056] In addition, the negative electrode 26 can be produced, for example, as follows.
[0057] First, a hydrogen storage alloy particle assembly, i.e., hydrogen storage alloy powder, a conductive material, a binder, and water are kneaded to form a negative electrode mixture paste. The obtained negative electrode mixture paste is applied to a negative electrode core material and dried. After drying, the negative electrode core material to which the hydrogen storage alloy particles and the like are attached is rolled and cut. Thus, a negative electrode 26 is formed.
[0058] The positive electrode 24 and the negative electrode 26 prepared as described above are wound in a spiral shape with the separator 28 interposed therebetween, thereby forming the electrode group 22 .
[0059] The electrode group 22 thus obtained is housed in the outer can 10. Next, a predetermined amount of alkaline electrolyte is injected into the outer can 10. Then, the outer can 10 housing the electrode group 22 and the alkaline electrolyte is sealed with the cover plate 14 having the positive terminal 20, thereby obtaining the battery 2 of the present invention. The obtained battery 2 is subjected to an initial activation treatment to be in a usable state.
[0060] The positive electrode for alkaline secondary batteries of the present invention contains anatase-type titanium oxide particles as a positive electrode additive. The titanium oxide particles have an average primary particle size of 5 nm or more and 10 nm or less and a BET specific surface area of 230 m 2 / g above 360m 2 / g or less particles, the titanium oxide particles contain 0.1% by mass or more of niobium. Moreover, the addition rate of the titanium oxide relative to the positive electrode active material nickel hydroxide is 0.1% by mass or more and 1.0% by mass or less. Such a positive electrode additive not only inhibits the reduction of the cobalt compound layer on the surface of the positive electrode active material particles, but also serves to make the reduced cobalt compound easy to return to the oxidized state, so that the alkaline secondary battery having a positive electrode containing the positive electrode additive can suppress the decrease in its capacity recovery rate to a lesser extent even if it is repeatedly placed in a high temperature environment in a state connected to a load. That is, according to the present invention, an excellent alkaline secondary battery is provided, which has tolerance even when it is repeatedly placed in a high temperature environment in a state connected to a load.
[0061] Example
[0062] 1. Battery manufacturing
[0063] (Example 1)
[0064] (1) Manufacturing of positive electrode
[0065] Nickel sulfate, zinc sulfate and cobalt sulfate are weighed in an amount such that zinc is 4% by mass and cobalt is 1% by mass relative to nickel, and added to a 1N sodium hydroxide aqueous solution containing ammonium ions to prepare a mixed aqueous solution. While stirring the obtained mixed aqueous solution, a 10N sodium hydroxide aqueous solution is slowly added to the mixed aqueous solution to allow a reaction to proceed, and during the reaction, the pH is stabilized at 13 to 14 to generate matrix particles having nickel hydroxide as the main component and zinc and cobalt dissolved therein.
[0066] The obtained matrix particles were washed three times with 10-fold amount of pure water, dehydrated and dried. The obtained matrix particles were spherical with an average particle size of 10 μm.
[0067] Next, the obtained matrix particles are put into an aqueous ammonia solution, the pH in the reaction is maintained at 9 to 10, and an aqueous cobalt sulfate solution is added. Thus, intermediate particles are obtained, which have a matrix particle as a core, cobalt hydroxide is precipitated on the surface of the core, and have a cobalt hydroxide layer with a thickness of about 0.1 μm. Then, in an environment of 80°C, in an oxygen-containing high-temperature air, the intermediate particles are convected in the presence of sodium hydroxide and subjected to a heat treatment for 45 minutes. Thus, the cobalt hydroxide on the surface of the intermediate particles becomes cobalt hydroxide oxide with high conductivity, and sodium is embedded in the layer of cobalt hydroxide oxide to form a conductive layer containing cobalt hydroxide oxide containing sodium. Then, the particles having the cobalt hydroxide oxide conductive layer are filtered, washed with water, and dried at 60°C. In this way, a powder of a positive electrode active material is obtained, which is an aggregate of positive electrode active material particles having a conductive layer formed of cobalt hydroxide oxide on the surface of the matrix particles.
[0068] Next, a positive electrode additive was prepared in the following manner.
[0069] A titanium oxide particle aggregate, i.e., a titanium oxide powder, was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 90 mass %, an average primary particle size of 5 nm, and a BET specific surface area of 360 m 2 / g.
[0070] Here, niobium was solid-dissolved in the titanium oxide particles, and 0.3 mass % of the niobium was contained in the form of niobium oxide. The amount of the solid-dissolved niobium oxide is shown in Table 1 as the niobium content.
[0071] Furthermore, a particle aggregate of yttrium oxide having an average particle size of 2.5 μm, namely, yttrium oxide powder was prepared, and then 0.8 parts by mass of the yttrium oxide powder was mixed with 0.2 parts by mass of titanium oxide to obtain a positive electrode additive powder.
[0072] Next, 1.0 parts by mass of positive electrode additive powder, 0.2 parts by mass of HPC powder, 0.3 parts by mass of PTFE dispersion and 30 parts by mass of water were mixed into 99.0 parts by mass of positive electrode active material powder to prepare positive electrode active material slurry, which was filled into foamed nickel as a positive electrode substrate and then dried. Thus, a positive electrode intermediate product in which positive electrode active material particles and the like were filled into foamed nickel was obtained.
[0073] The obtained intermediate product was rolled to a thickness of 0.52 mm, and then cut into a predetermined size to obtain a positive electrode 24 for AA size. In addition, the positive electrode contained 0.2 mass % of titanium oxide as a positive electrode additive and 0.8 mass % of yttrium oxide as a positive electrode additive relative to the positive electrode active material nickel hydroxide. This value is shown in Table 1 as the addition rate of titanium oxide to the positive electrode active material and the addition rate of yttrium oxide to the positive electrode active material.
[0074] (2) Manufacturing of hydrogen storage alloy and negative electrode
[0075] First, a rare earth component containing 12 mass % La and 88 mass % Sm is prepared. The obtained rare earth components Mg, Ni, and Al are weighed to form a mixture with a molar ratio of 0.90:0.10:3.40:0.10. The obtained mixture is melted in an induction melting furnace, the molten metal is poured into a mold, and then cooled to room temperature (about 25°C) to obtain an ingot of a hydrogen storage alloy.
[0076] Next, the ingot was subjected to a heat treatment at 1000°C for 10 hours in an argon atmosphere. After the heat treatment, the ingot was cooled to room temperature (about 25°C). A sample was taken from the ingot after the heat treatment and its composition was analyzed by high-frequency plasma spectrometry (ICP). As a result, the composition of the hydrogen storage alloy was (La 0.12Sm 0.88 ) 0.90 Mg 0.10 Ni 3.40 Al 0.10 .
[0077] Then, the heat-treated hydrogen storage alloy ingot was mechanically crushed in an argon atmosphere to obtain a collection of hydrogen storage alloy particles, i.e., hydrogen storage alloy powder. Here, the particle size of the obtained hydrogen storage alloy powder was measured using a laser diffraction scattering particle size distribution measuring device, and the result was that the volume average particle size (MV) of the hydrogen storage alloy particles was 60 μm.
[0078] To 100 parts by mass of the obtained hydrogen storage alloy powder, 0.4 parts by mass of sodium polyacrylate powder, 0.1 parts by mass of carboxymethyl cellulose powder, 1.0 parts by mass (converted to solid content) of styrene butadiene rubber (SBR) dispersion (50% by mass of solid content), 1.0 parts by mass of carbon black powder, and 30 parts by mass of water are added and kneaded to form a negative electrode mixture paste.
[0079] The negative electrode mixture paste was applied evenly and at a constant thickness on both surfaces of an iron perforated plate as a negative electrode core material. The perforated plate had a thickness of 60 μm and was nickel plated on its surface.
[0080] After the paste is dried, the perforated plate with the hydrogen storage alloy powder attached thereto is further rolled to increase the amount of alloy per unit volume, and then cut to obtain the negative electrode 26 for AA size.
[0081] (3) Manufacturing of nickel-hydrogen secondary batteries
[0082] The obtained positive electrode 24 and negative electrode 26 were wound into a spiral shape with a separator 28 interposed therebetween to obtain an electrode group 22. The separator 28 used in the manufacture of the electrode group 22 was a sulfonated separator obtained by sulfonating a polypropylene fiber nonwoven fabric with fuming sulfuric acid and then neutralizing it with an aqueous sodium hydroxide solution, and the thickness was 0.14 mm (unit area mass 60 g / m 2 ).
[0083] On the other hand, KOH, NaOH and LiOH were weighed and added to ion exchange water to prepare an alkaline electrolyte mainly composed of KOH, with a total concentration of 7.0N, 5.0N KOH, 1.0N NaOH and 1.0N LiOH.
[0084] Next, the electrode group 22 was placed in a bottomed cylindrical outer can 10, and 2.2 ml of the prepared alkaline electrolyte was injected. The opening of the outer can 10 was then sealed with a sealing body 11, thereby obtaining an AA-size nickel-hydrogen secondary battery 2 with a nominal capacity of 1100 mAh.
[0085] (4) Initial activation treatment
[0086] In an environment with a temperature of 25°C, the battery 2 was charged at 0.2C for 16 hours and then discharged at 0.4C until the battery voltage reached 1.0V. This charging and discharging operation was repeated 5 times to perform an initial activation process. In this way, the battery 2 was ready for use.
[0087] (Example 2)
[0088] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 0.3% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0089] (Example 3)
[0090] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 95% by mass, a niobium content of 0.3% by mass, an average primary particle size of 10 nm, and a BET specific surface area of 230 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0091] (Example 4)
[0092] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 99 mass %, a niobium content of 0.3 mass %, an average primary particle size of 10 nm, and a BET specific surface area of 230 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0093] (Example 5)
[0094] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 0.3% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, the addition rate of titanium oxide to the positive electrode active material is 0.1 mass %, and 0.9 mass parts of positive electrode additive powder, 0.2 mass parts of HPC powder, 0.3 mass parts of PTFE dispersion and 30 mass parts of water are mixed into 99.1 mass parts of positive electrode active material powder to prepare a positive electrode active material slurry. Except for this, a nickel-hydrogen secondary battery 2 in a usable state is prepared in the same manner as in Example 1.
[0095] (Example 6)
[0096] A titanium oxide powder is prepared as a collection of titanium oxide particles. The titanium oxide particles are anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 0.1% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0097] (Example 7)
[0098] An aggregate of titanium oxide particles, i.e., titanium oxide powder, was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 1.0% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0099] (Example 8)
[0100] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 0.3% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, the addition rate of titanium oxide relative to the positive electrode active material is adjusted to 1.0 mass %, and 1.8 mass parts of positive electrode additive powder, 0.2 mass parts of HPC powder, 0.3 mass parts of PTFE dispersion and 30 mass parts of water are mixed into 98.2 mass parts of positive electrode active material powder to prepare a positive electrode active material slurry. Except for this, a nickel-hydrogen secondary battery 2 in a usable state is prepared in the same manner as in Example 1.
[0101] (Comparative Example 1)
[0102] An aggregate of titanium oxide particles, i.e., titanium oxide powder, was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 99 mass %, a niobium content of 0.3 mass %, an average primary particle size of 15 nm, and a BET specific surface area of 100 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0103] (Comparative Example 2)
[0104] An aggregate of titanium oxide particles, i.e., titanium oxide powder, was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 99.9 mass %, a niobium content of 0.3 mass %, an average primary particle size of 150 nm, and a BET specific surface area of 13 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0105] (Comparative Example 3)
[0106] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were rutile titanium oxide particles having a purity (content after dehydration and drying) of 99 mass %, a niobium content of 0.3 mass %, an average primary particle size of 15 nm, and a BET specific surface area of 100 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0107] (Comparative Example 4)
[0108] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were rutile titanium oxide particles having a purity (content after dehydration and drying) of 99.9 mass %, a niobium content of 0.3 mass %, an average primary particle size of 150 nm, and a BET specific surface area of 8 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0109] (Comparative Example 5)
[0110] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 0.3% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, the addition rate of titanium oxide relative to the positive electrode active material is adjusted to 0.05 mass %, and 0.85 mass parts of positive electrode additive powder, 0.2 mass parts of HPC powder, 0.3 mass parts of PTFE dispersion and 30 mass parts of water are mixed into 99.15 mass parts of positive electrode active material powder to prepare a positive electrode active material slurry. Except for this, a nickel-hydrogen secondary battery 2 in a usable state is prepared in the same manner as in Example 1.
[0111] (Comparative Example 6)
[0112] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 99 mass %, a niobium content of 0.03 mass %, an average primary particle size of 10 nm, and a BET specific surface area of 230 m 2 / g, a nickel-hydrogen secondary battery 2 in a usable state was produced in the same manner as in Example 1 except for the above.
[0113] (Comparative Example 7)
[0114] A titanium oxide powder as an aggregate of titanium oxide particles was prepared. The titanium oxide particles were anatase-type titanium oxide particles having a purity (content after dehydration and drying) of 93% by mass, a niobium content of 0.3% by mass, an average primary particle size of 6 nm, and a BET specific surface area of 330 m 2 / g, the addition rate of titanium oxide relative to the positive electrode active material is adjusted to 2.0 mass %, and 2.8 mass parts of positive electrode additive powder, 0.2 mass parts of HPC powder, 0.3 mass parts of PTFE dispersion and 30 mass parts of water are mixed into 97 mass parts of positive electrode active material powder to prepare a positive electrode active material slurry. Except for this, a nickel-hydrogen secondary battery 2 in a usable state is prepared in the same manner as in Example 1.
[0115] [Table 1]
[0116]
[0117] 2. Evaluation of NiMH secondary batteries
[0118] (1) Unit capacity
[0119] For the batteries after the initial activation treatment of Examples 1 to 8 and Comparative Examples 1 to 7, charge at 0.1C charging current at 25°C until the nominal capacity reaches 160%. Then, leave it for 60 minutes. Next, discharge at 0.2C under the same environment until the battery voltage reaches 1.0V. Measure the discharge capacity of each battery at this time. Take this discharge capacity as the initial capacity. Then, calculate the mass of the active material and additives contained in the positive electrode to obtain the calculated mass. Next, divide the above initial capacity by the calculated mass to calculate the capacity per unit mass, that is, the unit capacity [mAh / g] of the positive electrode. The results are shown in Table 2 as unit capacity.
[0120] (2) Capacity recovery rate
[0121] For the batteries after the initial activation treatment of Examples 1 to 8 and Comparative Examples 1 to 7, charge at 0.1C in an environment of 25°C until the nominal capacity reaches 160%. Then, leave it for 60 minutes. Next, discharge at 0.2C in the same environment until the battery voltage reaches 1.0V. Measure the discharge capacity of each battery at this time. The discharge capacity at this time is taken as the initial capacity.
[0122] Again, the batteries of Examples 1 to 8 and Comparative Examples 1 to 7 were charged under the same environment at a charging current of 0.1 C until they reached 160% of the nominal capacity.
[0123] Next, a 2Ω resistor was connected to each battery so that each battery was connected to a load, and each battery in this state was placed in a thermostatic chamber with an internal temperature maintained at 60°C for 2 weeks.
[0124] After 2 weeks, each battery was taken out of the thermostatic chamber. Then, the resistor was removed from each battery. Then, each battery was charged at 0.1C at 25°C until the nominal capacity reached 160%. Then, it was left for 60 minutes. Next, it was discharged at 0.2C under the same environment until the battery voltage reached 1.0V. The discharge capacity of each battery at this time was measured. The discharge capacity at this time was taken as the capacity after placement.
[0125] Then, the capacity recovery rate was calculated by the following formula (I).
[0126] Capacity recovery rate [%] = capacity after storage / initial capacity × 100···(I)
[0127] This capacity recovery rate is shown in Table 2 as the first capacity recovery rate.
[0128] Next, each battery whose capacity after placement has been measured is charged at 0.1C at 25°C until the nominal capacity reaches 160%. Then, leave it for 60 minutes. Subsequently, connect a 2Ω resistor to each battery so that each battery is connected to a load. After that, place each battery in this state in a constant temperature chamber with an internal temperature maintained at 60°C for 2 weeks. After 2 weeks, take the battery out of the constant temperature chamber and remove the resistor. Then, charge it again at 0.1C at 25°C until the nominal capacity reaches 160%. Then, leave it for 60 minutes. Then, discharge it at 0.2C in the same environment until the battery voltage reaches 1.0V. Measure the capacity of each battery after discharge at this time.
[0129] The above-mentioned charging, placing under load, charging, and discharging were repeated 5 times. Then, the capacity recovery rate of each battery after the above-mentioned operation was calculated by formula (I). The obtained results are shown in Table 2 as the fifth capacity recovery rate.
[0130] The higher the value of the capacity recovery rate, the closer it is to the initial state. In particular, even if the battery with a high fifth capacity recovery rate is repeatedly placed in a state connected to a resistor, the reduction of cobalt hydroxide on the surface of the nickel hydroxide particles can still be suppressed, showing durability against repeated placement.
[0131] [Table 2]
[0132] [Table 2]
[0133]
[0134] (3) Investigation
[0135] (i) The above results show that the positive electrode comprises an anatase crystal structure, contains 0.1 mass % or more of niobium, has an average primary particle size of 5 nm or more and 10 nm or less, and has a BET specific surface area of 230 m 2 / g above 360m 2 / g or less of titanium oxide, and 0.1 mass % or more and 1.0 mass % or less of the titanium oxide is added to the positive electrode active material, and even if the battery including such a positive electrode is repeatedly placed in a high temperature environment in a state connected to a load, the decrease in the capacity recovery rate can be suppressed to a small extent. It can be said that for the case where the battery is repeatedly placed in a high temperature environment in a state connected to a load, it is effective to contain a positive electrode additive containing titanium oxide that meets the above conditions in the positive electrode to obtain the inhibitory effect of the decrease in the battery capacity recovery rate.
[0136] (ii) It is also known that when the purity of titanium oxide is within the range of 90 mass % to 95 mass %, when the battery is repeatedly placed in a high temperature environment with a load connected, good results can be obtained in suppressing the decrease in the capacity recovery rate. Therefore, it can be said that setting the purity of titanium oxide within the above range is effective in suppressing the decrease in the capacity recovery rate of the battery when it is repeatedly placed.
[0137] (iii) It can be seen from this that if the addition rate of titanium oxide to the positive electrode active material is greater than 1.0 mass %, and as high as 2.0 mass % as in Comparative Example 7, the unit capacity decreases. It can be said that setting the addition rate of titanium oxide to the positive electrode active material to 1.0 mass % or less is effective in maintaining the unit capacity.
[0138] The present invention is not limited to the above-mentioned nickel-hydrogen secondary battery, and various modifications are possible. For example, the present invention may be another alkaline secondary battery such as a nickel-cadmium secondary battery.
[0139] <Aspects of the Invention>
[0140] The first aspect of the present invention is a positive electrode for an alkaline secondary battery, comprising a positive electrode substrate and a positive electrode mixture supported on the positive electrode substrate, wherein the positive electrode mixture comprises a positive electrode active material, nickel hydroxide, and a positive electrode additive, wherein the positive electrode additive comprises titanium oxide particles having an anatase crystal structure, wherein the primary particles of the titanium oxide particles have an average particle size of 5 nm or more and 10 nm or less, and a BET specific surface area of 230 m 2 / g above 360m 2 / g or less, the titanium oxide particles contain 0.1 mass % or more of niobium oxide, and the addition rate of the titanium oxide to the nickel hydroxide is 0.1 mass % or more and 1.0 mass % or less.
[0141] Furthermore, a second aspect of the present invention is a positive electrode for an alkaline secondary battery, wherein the purity of the titanium oxide in the first aspect of the present invention is 90 mass % or more and 95 mass % or less.
[0142] The third aspect of the present invention is an alkaline secondary battery comprising an outer can and an electrode group housed in the outer can together with an alkaline electrolyte, the electrode group comprising a positive electrode and a negative electrode overlapped with a separator, the positive electrode being the positive electrode for an alkaline secondary battery described in the first aspect or the second aspect of the present invention.
[0143] Explanation of symbols
[0144] 2 NiMH secondary battery
[0145] 10 Outer can
[0146] 22 Electrode Group
[0147] 24 Positive electrode
[0148] 26 Negative electrode
[0149] 28 Spacer
Claims
1. A positive electrode for an alkaline secondary battery, comprising a positive electrode substrate and a positive electrode mixture supported on the positive electrode substrate, The positive electrode mixture comprises a positive electrode active material, nickel hydroxide, and a positive electrode additive. The positive electrode additive comprises Titanium oxide particles with anatase crystal structure. The titanium oxide particles have an average primary particle size of 5 nm to 10 nm and a BET specific surface area of 230 m 2 / g above 360m 2 / g or less, and the titanium oxide particles contain 0.1 mass % or more and 1.0 mass % or less of niobium as a solid solution, The addition rate of the titanium oxide to the nickel hydroxide is 0.1 mass % or more and 1.0 mass % or less.
2. The positive electrode for an alkaline secondary battery according to claim 1, wherein The purity of the titanium oxide is 90 mass % or more and 95 mass % or less.
3. An alkaline secondary battery comprising an outer can and an electrode group housed in the outer can together with an alkaline electrolyte, The electrode group includes a positive electrode and a negative electrode stacked with a separator, The positive electrode is the positive electrode for an alkaline secondary battery according to claim 1 or 2.
Citation Information
Patent Citations
Alkaline cell
CN1219778A
Alkaline secondary battery positive electrode material and alkaline secondary battery
CN1976098A
Nickel positive electrode and alkaline secondary battery using it
JP2002025549A
Alkaline storage battery
JP2004031292A